Renal complications following COVID-19 vaccination: A narrative literature review - Vijaya Krishna Prasad Vudathaneni; Swetha Bharathi Nadella; Duddukuri Hema; Ramanarayana Boyapati (Wolters Kluwer Medknow Publications, 2023)
Background: Renal complications have previously been reported with various vaccinations, including those for influenza and hepatitis. On a similar note, a spectrum of nephrological complications, both de novo, and flare-ups, were reported after immunization with various coronavirus disease 2019 (COVID-19) vaccines, causing concerns among patients as well as physicians. Materials and Methods: A systematic search of the literature published on renal complications seen post-COVID-19 vaccination was performed up to April 2022 using electronic databases such as PubMed and Google Scholar. Result: Immunoglobulin A (IgA) nephropathy, minimal change disease, glomerulonephritis, acute kidney injury, nephrotic syndrome, and anti-neutrophil cytoplasmic antibody-associated vasculitis were some of the renal complications reported upon administration of COVID-19 vaccines. The causality and underlying pathogenic mechanisms linking these complications and COVID-19 vaccination remain unclear. Nonetheless, a temporal relationship has been established with dysregulated T-cell response, transient systemic pro-inflammatory cytokine response, molecular mimicry, delayed hypersensitivity reaction to the vaccine, and other mechanisms such as hyperresponsive IgA, dysregulation of neutrophil extracellular traps were hypothesized as the possible mechanisms linking renal complications and COVID-19 vaccination. Conclusion: This review emphasizes the need for rigorous surveillance and reporting of the adverse events following COVID-19 vaccination and explores the underlying mechanisms instigating these renal complications in individuals vaccinated against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2).